1977
DOI: 10.1021/ic50176a035
|View full text |Cite
|
Sign up to set email alerts
|

Chemistry of tetravalent nickel and related species. 3. Characterization and cyclic voltammetry of new [NiN6] species based on tridentate ligands

Abstract: 22) In Tables II and III and throughout the paper when compounds in those tables are referred to, an arabic number is used to indicate the olefin, the arabic number followed by a lower case "a" indicates the Ni(r-BuNC)2 complex of that olefin and "b" indicates the Ni(PPh3)2 complex of that olefin; i.e., 20 is acrylonitrile, 20a is Ni(r-BuNC)(CH2CHCN) and 20b is Ni(PPh3)2(CH2CHCN). ( 23) For an ethylene complex, the symmetry would be and vNC' and i^c2 would be Aj and Bi. Substitution reduces the symmetry to C2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

1978
1978
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(20 citation statements)
references
References 13 publications
3
17
0
Order By: Relevance
“…The results are summarized in Table 2 with the complexes studied in the literature for comparing. It is clearly stated in the literature that oxime comparison metal complexes give redox signals involving both higher and lower oxidation states of the metal depending on the coordination environment of metal center and involving ligand reduction/oxidation processes recorded at very high negative/positive potentials [15, [27][28][29][30][31]. Electrochemical behavior of the complexes studied here are in harmony with the literature.…”
Section: Electrochemical Measurementssupporting
confidence: 86%
“…The results are summarized in Table 2 with the complexes studied in the literature for comparing. It is clearly stated in the literature that oxime comparison metal complexes give redox signals involving both higher and lower oxidation states of the metal depending on the coordination environment of metal center and involving ligand reduction/oxidation processes recorded at very high negative/positive potentials [15, [27][28][29][30][31]. Electrochemical behavior of the complexes studied here are in harmony with the literature.…”
Section: Electrochemical Measurementssupporting
confidence: 86%
“…The syntheses of the bis species Ni(HT)2 (CI0 4)2 and Ni(T)2 (CI0 4)2 closely follow [13] the methods used for the hexad entate analogues. The complexes of 2 are however more stable than those of 4, as expected.…”
Section: Rxnoh Hon Rmentioning
confidence: 88%
“…The behaviour of HT complexes is grossly similar [13] except that Ni(HTW is unstable in acidic media and decomposes at the rate of 0.16 S-l to form Ni(H20)~+. The HY complex [24] displays the couple (3) in the pH range 5-7 with E~98 of 0.68 V vs SCE.…”
Section: Cyclic Voltammetry In Aqueous Solution: Electroprotic Equilimentioning
confidence: 91%
See 1 more Smart Citation
“…It is generally observed that for Ni(II)/Ni(I) redox couples, larger numbers of thioether donors tend to relatively stabilize the formation of Ni(I) [7,56 -58], whereas larger numbers of imino-nitrogen donors tend to stabilize Ni(III) [58,59]. Higher oxidation states of nickel are commonly accessible in systems with oximato-nitrogen donors, as a result of the coulombic influence of the negative charge on the HOMO energy [60] and of s-donation effects [52].…”
Section: Electron Spin Resonancementioning
confidence: 99%